2012
DOI: 10.1021/ef2011645
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Atmosphere on the Transformation of Alkali and Alkaline Earth Metallic Species during Rice Straw Thermal Conversion

Abstract: The influence of the atmosphere on the transformation of alkali and alkaline earth metallic (AAEM) species during rice straw thermal conversion was investigated by a fixed-bed reactor at 1073, 1173, and 1273 K. Two types of atmospheres were considered: 100% (v/v) N 2 to simulate pyrolysis and 1% (v/v) O 2 in N 2 balance to simulate combustion. The release of the AAEM species during pyrolysis and combustion of the rice straw was quantified by a mass balance based on the weight measurements and inductively coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 23 publications
2
66
0
Order By: Relevance
“…It can be concluded that the high temperature and short residence time accelerate the bio-oil yield, which agrees with the results by Onay et al (Onay and Kockar, 2003). On the other hand, higher temperatures result in more release of mineral species, such as Na, Mg, K and Ca existed in SS and WS into bio-oil (Zhang et al, 2012). Besides, the bio-oil yield obtained in a drop-tube reactor in this work is higher than that obtained by other researchers in fixed-bed reactors for the pyrolysis of sewage sludge or biomass (Zuo et al, 2014;Han et al, 2015;Samanya et al, 2012).…”
Section: Product Distributions Of Ss and Ws At Different Temperaturessupporting
confidence: 90%
“…It can be concluded that the high temperature and short residence time accelerate the bio-oil yield, which agrees with the results by Onay et al (Onay and Kockar, 2003). On the other hand, higher temperatures result in more release of mineral species, such as Na, Mg, K and Ca existed in SS and WS into bio-oil (Zhang et al, 2012). Besides, the bio-oil yield obtained in a drop-tube reactor in this work is higher than that obtained by other researchers in fixed-bed reactors for the pyrolysis of sewage sludge or biomass (Zuo et al, 2014;Han et al, 2015;Samanya et al, 2012).…”
Section: Product Distributions Of Ss and Ws At Different Temperaturessupporting
confidence: 90%
“…Previous studies also reported that the formation of K-Si species following the R9 becomes significant at the combustion temperature above 900℃ [11,41]. K2SO4 (s) could be evaporated from 1000℃ and above [12], resulting in a further loss of K content from solid residues.…”
Section: Stage 3: the Second-step Release (Above 700°c)mentioning
confidence: 91%
“…When the final temperature exceeds 800℃, the abundant decomposition and evaporation of inorganic K compounds (like K2CO3 and K2SO4) will dominate the released volatile K species. Meanwhile, the retention of K will occur through reactions between Si and the captured K to form thermally-stable K silicates [11,41].…”
Section: Proposal Of a Comprehensive Temperature-dependent K-transition Pathwaymentioning
confidence: 99%
“…XRD analysis (see Figure 1.a) confirmed that no carbonates were present in the crystalline phase of the SSA samples obtained at incineration temperatures above 650 °C. Several authors found that the release of alkali and alkaline earth metals (specifically Ca, K, Mg and Na) from biomass fuels in general increases with increasing incineration temperature [34][35][36][37]. Yet, in this work, the Ca, K, Mg and Na concentration in the SSA remained relatively constant with increasing incineration temperature (5.45 -5.76% of DM, 1.94 -2.02% of DM, 1.24 -1.32% of DM and 0.34 -0.39% of DM for a temperature increase from 550 to 1100 °C, respectively).…”
Section: Ssa Characterizationmentioning
confidence: 99%
“…Yet, in this work, the Ca, K, Mg and Na concentration in the SSA remained relatively constant with increasing incineration temperature (5.45 -5.76% of DM, 1.94 -2.02% of DM, 1.24 -1.32% of DM and 0.34 -0.39% of DM for a temperature increase from 550 to 1100 °C, respectively). This is related to the high concentration of Si in the SS and hence also in the SSA (18.79 -19.58% of DM), retaining Ca, K, Mg and Na in the silicate fraction [34][35][36][37]. XRD analysis (see Figure 1.d) indeed showed that these alkali and alkaline earth metals are bound in the silicate fraction as diopside (CaMgSi2O6), microcline (KAlSi3O8), muscovite (KAl3Si3O10(OH,F)2), plagioclase ((Na,Ca)(Si,Al)4O8) and smectite-related minerals (e.g., (Na,Ca)0.3(Al,Mg)2Si4O10(OH)2.xH2O), all having high boiling points.…”
Section: Ssa Characterizationmentioning
confidence: 99%